Lipopolysaccharide Complexes with Pasteurella haemolytica Leukotoxin - Li, Jun (American Society for Microbiology, 1999)
The presence of lipopolysaccharide (LPS) in gram-negative bacterial repeats-in-toxin (RTX) toxin preparations, as well as the harsh conditions required to remove it, suggests that LPS may complex with RTX toxins. Concentrated culture supernatant (CCS) preparations of the RTX toxin Pasteurella haemolytica leukotoxin (LKT) contained LKT and LPS as the most prominent components, with LKT and LPS constituting ≈30 and 50% of the density of the silver-stained fraction on sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), respectively. CCS LKT contained 3.69 ± 0.46 mg of LPS per mg of protein, which was estimated to indicate an LPS/LKT molar ratio of ≈60:1. Subjection of the CCS LKT to preparative SDS-PAGE resulted in separation of LPS from LKT as detected by silver-stained analytical SDS-PAGE; however, the LKT fraction (SDS-PAGE LKT) contained significant endotoxin activity as detected by the Limulus amebocyte lysate assay. Subjection of the SDS-PAGE LKT to a second preparative SDS-PAGE run resulted in a reduction of the LPS/LKT molar ratio to 1:20. The target cell specificity of LKT for bovine leukocytic cells was retained by the SDS-PAGE LKT, and isolated LPS at comparable concentrations to that in CCS LKT exhibited no leukolytic activity. Addition of isolated LPS back to SDS-PAGE LKT resulted in reconstitution of an LPS-LKT complex. Immediately following reconstitution of the LPS-LKT complex, there was minimal change in leukolytic activity of the complex, but following 9.5 h at temperatures from −135 to 37°C, the LPS-LKT complex exhibited increased leukolytic activity and thermal stability compared to SDS-PAGE LKT. Therefore, it appears that LPS complexes with LKT, resulting in enhanced and stabilized leukolytic activity.